The history of Toponymic terminology in Algeria: The Tlemcen region as a casestudy (Lex localis - Journal of Local Self-Government, 2025)
This study examines the history of toponymic terms (place names) in the Tlemcen region of western,Algreia. The study is divided into two part : theoretical part reviews the concept of toponymy and itsmain classsifications, while providing an introductory overview of the studied region. The applied partpresents a comprehensive academic glossary covering various branches of toponymy, including :oronyms (mountain names), hydronyms (water body names), agiotoponmys (names of inhabitedplaces), and other classifications.The study reveals the successive civilizations of the region and their clear impact on the toponymicfabric, it concludes that place names in Tlemcen constitute a living record of collective memory,reflecting the cultural diversity and cross-cultural interaction that has characterized this strategicallyimportant region throughout the ages.